Kajian Desain Struktur Beton Bertulang Dengan Struktur Baja (Studi Kasus Pada Pembangunan Gedung H Unitomo) - Batak, Inggrid Loiza; Zuraidah, Safrin; Hastono, Budi (Department of Civil Engineering, Dr. Soetomo University, 2019)
Recently, a structure that is generally applied to the construction of multi-storey buildings is reinforced concrete structure. Structural steel is rarely used nowadays, yet in fact, the steel structures are still able to compete with reinforced concrete structures. Therefore, this study aims to determine the exact profile dimensions and the comparison of material prices between steel structures and reinforced concrete structures for columns and beams in redesigning H Building of Dr. Soetomo University, Surabaya. The WF profile steel will be used in this redesigning project. The structure is modeled using AutoCAD, and then imported into SAP2000 software. Modeling structure consists of columns, primary beams and secondary beams. The loads reviewed from the design are dead load, live load, wind load and seismic load. From the results of design review obtained, the overall strength of structure rearrangement is safe and it is obtained the beam profile dimensions of B1 WF 600x200x12x20, B2 WF 400x300x9x14 profile, B3 WF 400x300x9x14 profile, B4 WF 350x200x8x12 profile, and B5 WF 175x125x 5.5x8 profile, K1 WF 400x400x18x28 column profile, and K2 WF 400x400x21x21 column profile. The use of steel structures as a substitute for reinforced concrete structures for columns and beams in the building is a way more expensive with the percentage of steel structure 149.13% more expensive than reinforced concrete structure.